Synthesis of β-Arylbutenolides Mediated by BF 3·oMe 2 - Finêncio, Beatriz M. [UNESP]; Santos, Fernanda A. [UNESP]; Laurentiz, Rosangela S. [UNESP] (Thieme, 2022)
The reaction of phenols or aryl ethers with tetronic acid mediated by BF3·OMe2 was investigated. This strategy allowed for the preparation of β-(hydroxyaryl)butenolides and β-arylbutenolides in a single step in a simpler way than previously reported synthetic methods.
Keywords: aromatic electrophilic substitution; butenolides; rubrolides; synthons; tetronic acid